Descripción inmunohistoquímica de la encefalitis en bovinos brasileños naturalmente infectados con el herpesvirus bovino tipo 5 (HVB-5) - Pedraza, F. J.; Schild, A. L.; Alessi, A. C. [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2008)
Twelve cases of viral meningoencephalitis in Brazilian cattle were submitted to immunohistochemical analysis for inflammatory response description. All the cases showed severe neurological signs followed by death. Mild to moderate histological inflammatory changes in the brain and cerebellum characterized the neurological infection showing meningitis, mononuclear perivascular cuffing, gliosis, haemorrhage, and macrophages (gitter cells) accompanying great areas of malacia. None of the cases showed intranuclear inclusion bodies. However, in five of them it was possible to isolate the BoHV-5. In order to collect data to allow the description of the inflammatory response in these cases, brain samples from all of the cases were analyzed by immunohistochemistry using polyclonal antibodies against CD3 to detect T cells, and against GFAP to detect astrocytes. On the other hand, monoclonal antibodies were used against BLA to detect B cells and, against MAC 387 to detect macrophages. The results indicate different degrees of prominent astrocytic response, and at the same time, T lymphocytes constituted a high percentage of the mononuclear cells which characterized the inflammatory response.
Immunohistochemical description of encephalitis in Brazilian cattle naturally infected with bovine herpes virus type 5 (BoHV-5)
Keywords: BoHV-5; Bovine polioencephalomalacia; Viral encephalitis; Bos; Bovinae; Bovine herpesvirus 5; Herpesviridae